2019
DOI: 10.1101/591073
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AMPK-independent LKB1 activity is required for efficient epithelial ovarian cancer metastasis

Abstract: Epithelial ovarian cancer (EOC) spreads by direct dissemination of malignant cells and multicellular clusters, known as spheroids, into the peritoneum followed by implantation and growth on abdominal surfaces. Using a spheroid model system of EOC metastasis, we discovered that Liver kinase B1 (LKB1), encoded by the STK11 gene, and its canonical substrate AMP-activated protein kinase (AMPK) are activated in EOC spheroids, yet only LKB1 is required for cell survival. We have now generated STK11-knockout cell lin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Furthermore, work in our laboratory identified recently that LKB1-deficient EOC spheroids still retain the capacity to induce p-AMPK through CAMKKβ activity [26]. This finding together with our results herein suggest a crucial role for CAMKKβ in regulating p-AMPK levels in this disease.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, work in our laboratory identified recently that LKB1-deficient EOC spheroids still retain the capacity to induce p-AMPK through CAMKKβ activity [26]. This finding together with our results herein suggest a crucial role for CAMKKβ in regulating p-AMPK levels in this disease.…”
Section: Discussionsupporting
confidence: 85%
“…LKB1 is a highly-conserved serine-threonine kinase that typically functions as a regulator of cellular metabolism within the AMPK signaling axis [25]. Surprisingly, recent work from our laboratory identified that EOC spheroids lacking LKB1 expression by CRISPR-mediated STK11 knockout sustain elevated p-AMPK suggesting alternative kinase(s) target AMPK in our system [26].…”
Section: Pharmacologic Inhibition Of Camkkβ Reduces Ampk Phosphorylatmentioning
confidence: 87%
“…Dormant HGSOC cells are characterized by similar metabolic changes, EMT, and cytokine signaling as dormant cancer cells from other disease sites (3, 11). Mechanisms that mediate their dormant properties include AMPK-LKB1 signaling that induces autophagy (12, 13), STAT3 and FAK for survival and chemoresistance (14, 15), and DYRK1A signaling to arrest proliferation (16). Unfortunately, therapeutic approaches to target these pathways in ovarian cancer have yet to emerge, indicating that more candidates are needed.…”
Section: Introductionmentioning
confidence: 99%